Medium‐term protective effects of quality early childhood education during the COVID‐19 pandemic in Ghana. Issue 6 (12th July 2022) - Wolf, Sharon; Aurino, Elisabetta; Suntheimer, Noelle M.; Avornyo, Esinam A.; Tsinigo, Edward; Behrman, Jere R.; Aber, J. Lawrence
Abstract: The COVID‐19 pandemic led to extended school closures globally. Access to remote learning opportunities during this time was vastly unequal within and across countries. Higher‐quality early childhood education (ECE) can improve later academic outcomes, but longer‐term effects during crises are unknown. This study provides the first experimental evidence of how previously attending a higher‐quality ECE program affected child engagement in remote learning and academic scores during pandemic‐related school closures in Ghana. Children ( N = 1668; 50.1% male; M age = 10.1 years; all Ghanaian nationals) who attended higher‐quality ECE at age 4 or 5 years had greater engagement in remote learning ( d = .14) in October 2020, but not better language and literacy and math scores. Previous exposure to higher‐quality ECE may support educational engagement during crises.